GOVERNMENT INTERVENTION IN DETERMINING PRICES ACCORDING TO IBN TAIMIYAH’S - Khanifah Nurfaizah (Airlangga International Journal of Islamic Economics and Finance, 2019)
Government intervention in pricing, has always been debated among economists. Islam as a religion which the last has a good economic outlook in terms of micro, macro as well as domestic scale, regional and even international. Prophet was the first in Taimiyah’s book by the public regarding the intervention price, at the time of the Prophet give answers like the following hadith "From Anas bin Malik, he said: the price of goods once expensive at the time of the Prophet. then people said: Messenger of Allah, the prices to be expensive, set a standard price for us, the Messenger of Allah said: Surely it is God who sets the price, holding and distributing rizki, and indeed just hoped that I could meet Allah in a state no one among you who prosecute me because of the injustice in the bloodshed (killer) and treasures. "(HR. Abu Dawud, Ahmad, Tirmidhi and Ibn Majah)" based on the tradition is causing debate among scientists, they have a different view of these traditions. One of them Muslim scientist Ibn Taymiyyah who see his government intervention in pricing, Ibn Taymiyyah was found Ibn Taymiyyah, found the price to be considered by the forces of supply and demand. Due to a shortfall in production or a decrease in imports of goods requested. So, if the need to increase the number of goods, while the ability to provide it decreases, prices will naturally increased. Determines prices by Ibn Taymiyyah can be divided into two types, namely injustice and tyranny of elements. found the price to be considered by the forces of supply and demand. due to a shortfallin production or a decrease in imports of goods requested. So, if the need to increase the number of goods, while the ability to provide it decreases, prices will naturally increased. Determines prices by Ibn Taymiyyah can be divided into two types, namely injustice and tyranny of elements. found the price to be considered by the forces of supply and demand. due to a shortfall in production or a decrease in imports of goods requested. So, if the need to increase the number of goods, while the ability to provide it decreases, prices will naturally increased. Determines prices by Ibn Taymiyyah can be divided into two types, namely injustice and tyranny of elements. Intervention pricing allowed even obligatory in Islam for the benefit of welfaresociety.